2023
DOI: 10.1039/d3qi00769c
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the coordination microenvironment of uranyl compounds to enhance photocatalytic CO2 reduction

Zhi-Wei Huang,
Shu-Wen An,
Kong-Qiu Hu
et al.

Abstract: Rationalizing of the use of depleted uranium resources has always been of great interest. Herein, we have obtained two actinide compounds by regulating the ratio of each component in the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Two UO 8 hexagonal bipyramids are connected by edge-sharing to form a [(UO 2 ) 2 (μ 2 -O) 2 O 8 ] 4– binuclear uranyl unit (Figure a). In the two uranium centers, the lengths of the axial UO bond are in the range of 1.712–1.846 Å, and the lengths of the U–O bond in the equatorial plane are in the range from 2.320 to 2.535 Å, all of which are equal to the distances reported. Binuclear uranyl units are linked by quadridentate ligands via each chelating four carboxyl groups, which further extends to build a monolayer with ring structures (Figure b). Finally, such layers are stacked by π···π interaction forming a three-dimensional supramolecular network structure with an interlayer spacing of about 3.3 Å (containing the van der Waals radii) (Figure c).…”
Section: Resultsmentioning
confidence: 81%
“…Two UO 8 hexagonal bipyramids are connected by edge-sharing to form a [(UO 2 ) 2 (μ 2 -O) 2 O 8 ] 4– binuclear uranyl unit (Figure a). In the two uranium centers, the lengths of the axial UO bond are in the range of 1.712–1.846 Å, and the lengths of the U–O bond in the equatorial plane are in the range from 2.320 to 2.535 Å, all of which are equal to the distances reported. Binuclear uranyl units are linked by quadridentate ligands via each chelating four carboxyl groups, which further extends to build a monolayer with ring structures (Figure b). Finally, such layers are stacked by π···π interaction forming a three-dimensional supramolecular network structure with an interlayer spacing of about 3.3 Å (containing the van der Waals radii) (Figure c).…”
Section: Resultsmentioning
confidence: 81%
“…13–16 In particular, metal-coordinated N-doped carbon-supported SACs (M–N–C, M = transition metals) have emerged as promising CO 2 RR electrocatalysts, featuring long-term stability, reproducible performance, and potential for large-scale synthesis. 17–21 Prior to these catalysts, metallic tetraazamacrocycles, including porphyrins, phthalocyanines, and biphenanthrolinic hexaazacyclophanes, with similar M–N 4 coordination structures have attracted attention towards catalysis for the CO 2 RR in the 1970s. 22 As early as 1974, Meshitsuka first observed that graphite-supported cobalt or nickel phthalocyanine electrodes showed the polarization curves in aqueous electrolytes with CO 2 ; the reduction product, however, was not identified.…”
Section: Introductionmentioning
confidence: 99%